AUGMENTED REALITY IN TEACHER EDUCATION. A FRAMEWORK TO SUPPORT TEACHERS' TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE - Josef Buchner; Jörg Zumbach (Italian Journal of Educational Technology, 2020)
In this article the use of Augmented Reality (AR) as an educational technology in classroom applications and teacher training is suggested. AR is a combination of real-world information with digital information overlaid. A review of the research literature on AR learning environments reveals that in most studies AR contributes to successful learning and increased motivation. An evaluation study reveals that teachers’ ability of self-concept for implementing AR within their classrooms is closely related to educational technology and the technology itself in general. Here, teachers need orchestrated support for implementing AR in classrooms. Subsequently, a model for design and implementation of AR classroom application is suggested. These suggestions are illustrated by some exemplary AR classroom learning environments. This paper closes with recommendations for future research, in which more basic and controlled experimental research is needed in order to get a valid impression about the benefits of AR as classroom technology.